2017
DOI: 10.1109/tuffc.2017.2679160
|View full text |Cite
|
Sign up to set email alerts
|

Vibrational Responses of Bound and Nonbound Targeted Lipid-Coated Single Microbubbles

Abstract: One of the main challenges for ultrasound molecular imaging is acoustically distinguishing nonbound microbubbles from those bound to their molecular target. In this in vitro study, we compared two types of in-house produced targeted lipid-coated microbubbles, either consisting of 1,2-dipalmitoyl-sn-glycero-3-phosphocholine, C16:0 (DPPC) or 1,2-distearoyl-sn-glycero-3-phosphocholine, C18:0 (DSPC) as the main lipid, using the Brandaris 128 ultrahigh-speed camera to determine vibrational response differences betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 50 publications
(100 reference statements)
1
5
0
Order By: Relevance
“…Our data is in agreement with the current knowledge that clustering happens quickly (ms) [61]. The range of microbubble sizes (3.8-5.4 µm) leading to clustering were both within, and slightly outside, of resonance; however, that was determined at 50 kPa [58]. Increasing pressure is known to (linearly) dampen resonance frequency [62].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Our data is in agreement with the current knowledge that clustering happens quickly (ms) [61]. The range of microbubble sizes (3.8-5.4 µm) leading to clustering were both within, and slightly outside, of resonance; however, that was determined at 50 kPa [58]. Increasing pressure is known to (linearly) dampen resonance frequency [62].…”
Section: Discussionsupporting
confidence: 91%
“…However, other sonobactericide studies used similarly sized microbubbles [50,51,57], and the mean diameter was in range of the clinically approved human albumin-coated microbubbles (Optison, mean diameter (range) 3-4.5 µm). It is of potential importance that this larger size is closer to resonance frequency, at 2 MHz [58], which could translate to a more efficacious sonobactericide treatment, since a larger microbubble population would achieve maximum excursion amplitude. The microbubble concentration used in this study was chosen to maximize sonoporation potential, due to the sheer number of cells (~7000), and was supported by Dong et al [50], who observed that a higher microbubble concentration led to enhanced bacterial PI uptake in biofilms.…”
Section: Discussionmentioning
confidence: 99%
“…It has been observed that as the initial stand-off distance increases, biofilm disruption, sonoporation and cytoskeleton disassembly decrease (Goh et al 2015;Wang et al 2018b). Moreover, microbubble dynamics also depend on the distance from and material properties of a surface (Overvelde et al 2011;van Rooij et al 2017).…”
Section: Bacteriamentioning
confidence: 99%
“…The direct impact of microbubble cavitation on cellular barriers has been investigated in vitro on various cell lines including cancer cell lines and primary endothelial cells [8,[28][29][30][31][32][33][34][35][36][37]. The latter is the most biologically relevant as microbubbles cannot extravasate from the blood stream after intravenous injection.…”
Section: The Cellular Barrier and Cellular Homeostasismentioning
confidence: 99%